APPLICATION OF SCIENTIFIC INQUIRY LEARNING MODEL TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF CLASS X STUDENTS IN VIRUS MATERIALS IN SMA NEGERI 11 BANDA ACEH - Ariannisa Ramadhanti; Muhibbuddin Muhibbuddin; Andi Ulfa Tenri Pada; Asiah Asiah; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Student learning motivation is classified as less optimal due to several reasons, namely students tend to participate less during question and answer activities from their teacher and pay less attention to the teacher when delivering material in the learning process. The purpose of this research is to find out the application of the Scientific Inquiry Learning Model in increasing motivation and student learning outcomes on virus material. This study uses a pretest-posttest control group design experimental method. The parameters used are learning motivation and student learning outcomes collected through pretest and posttest. The data obtained were then tabulated and analyzed using the N-Gain formula to find out the improvement in learning outcomes. Next, a statistical analysis was carried out in the form of the Independent sample t-test and the Mann-Whitney test to determine differences in motivation scores and learning outcomes in the experimental and control class students. For learning motivation, the data obtained were also analyzed by the percentage of scores per indicator to determine its categorization. The results obtained for Independent sample t-test of the average learning motivation, obtained tcount = 5.07 ttable = 4.1. For categorization, the experimental class received an average of